The Application of Musyarakah Floor Stocking-i: A Case Study of Bank Muamalat Malaysia Berhad - Jaafar, M. N.; Mohd Taher, M. S. I.; Kamarudin, M. F. (Universiti Sains Islam Malaysia, 2024)
In Islamic banking, there are two major modes of financing namely via debt and equity respectively. It was reported that most of the financial institutions in Malaysia are applying the former model of financing in their products such as Bay’al-Inah, Murabahah, Bay’Bithaman Ajil, Tawarruq and etc as compared to the latter model of financing ie Musyarakah and Mudarabah. The main reason for the financial institutions avoiding equity financing is mainly due to their profit oriented objective which attribute to avoiding the element of moral hazard, loss and dishonesty respectively which could be apparently found in the equity mode of financing. Nevertheless, most of the Islamic scholars are very much preferred equity financing as it seems to reflect most faithfully principles of the Shariah. In other word, the equity financing makes the nature of Islamic banking more visible. In addition, Islamic finance also stands for a system of equity sharing and stake taking and it operates on the principle of variable return based on actual productivity and the performance of the projects. Despite high risk features in the equity financing, Bank Muamalat has successfully introduce as such model under the product of Musyarakah Floor Stocking. Therefore, this paper will discuss the concept paper of Bank Muamalat Musyarakah Floor Stocking which is applying profit sharing principle.